Rag Bodies, Empty Subjects - Aznar Almazán, Yayo; Iribas, Ana (Re-visiones, 2024)
It is evident that disciplinary societies have contributed a great deal to the invisibility of our bodies, but the fact remains that this "disembodiment" can also be, to a greater or lesser extent, the visible symptom of a void in the subject in the contemporary world. The relation of Tony Oursler’s work with the Dissociative Identity Disorder allows to extend this clinical pathology to a reflection on the vacuity of subjects in a world haunted by the images we all know, performative images that offer multiple identities with which to "fill" that gap. The performativity of the images in the construction of "alternate" subjectivities is, in this case, very obvious, and the specular relation of the subjects with the mass-media have consequences that have not escaped the analysis of important thinkers.